Carnegie International 1988 - Caldwell, John; Carnegie International 1988, Pittsburgh (Pittsburgh : The Carnegie Museum of Art, 1988)
Anselmo, Giovanni ; Armajani, Siah ; Artschwager, Richard ; Baselitz, Georg ; Baumgarten, Lothar ; Beuys, Joseph ; Bleckner, Ross ; Blume, Anna & Bernard ; Clemente, Francesco ; Fabro, Luciano ; Fischli & Weiss ; Förg, Günther ; Fritsch, Katharina ; Halley, Peter ; Horn, Rebecca ; Kapoor, anish ; Kiefer, Anselm ; Kirkeby, Per ; Koons, Jeff ; Kounellis, Jannis ; Laib, Wolfgang ; Levine, Sherrie ; Marden, Brice ; Martin, Agnes ; Murray, Elizabeth ; Nauman, Bruce ; Polke, Sigmar ; Richter, Gerhard ; Rothenberg, Susan ; Ryman, Robert ; Schnabel, Julian ; Shapiro, Joel ; Solano, Susana ; Trockel, Rosemarie ; Twombly, Cy ; Vaisman, Meyer ; Viola, Bill ; Wall, Jeff ; Warhol, Andy
Carnegie International 88, The Carnegie Museum of Art, Pittsburgh, November 5, 1988 - January 22, 1989
boek